THE INFLUENCE OF MINIMUM WAGE AND MANPOWER TOWARD DOMESTIC INVESTMENT IN NORTH SUMATRA - Nasution, Yenni Samri Juliati; Siregar, Retnawati (Accounting and Business Journal; Vol 2 No 2 (2020): ACCOUNTING AND BUSINESS JOURNAL, 2020)
Direct and indirect economic development will be followed by development in various sectors such as infrastructure, education, health, transportation, wages, exports and manpower which are all related to economic growth that will improve the welfare of the community. Investment activities are expected to have a positive effect on economic growth, the presence of this investment will drive and be driver by accelerating development widely. North Sumatra is one of the provinces which has a geographic and demographic location and has skill human resources and good natural resources in all sectors. This research uses a quantitative approach with secondary data through the official website of Central Bureau of Statistics with 18 samples, the data is processed with Eviews 8 program and data analysis techniques uses multiple linear regression analysis. Based on the results of the analysis, the GRDP, minimum wages and manpower have a significant effect partially or simultaneously on domestic investment in North Sumatra province